Equity and public governance in health system reform Challenges and opportunities for China - Brixi, Hana (The World Bank, 2011)
Achieving the objective of China's current health system reform, namely equitable improvements in health outcomes, will be difficult not least because of the continuously growing income disparities in the country. The analysis in this paper shows that since 2000, disparity in selected health outcomes has been declining across provinces, largely due to earmarked central government allocations. By contrast, public expenditure on health is increasingly regressive (positively correlated with local income per capita) across provinces, and across prefectures and lower levels within provinces. The increasing inequity in public expenditure at sub-national levels indicates that incentives, responsibilities, and resources at sub-national levels are not well aligned with China's national priorities. To address the weaknesses in equity and efficiency that characterize China's health system and health outcomes, China's health system reform may require complementary reforms to improve governance for public service delivery across sectors